Radionuclide Bone Scintigraphy: An Interesting Case Report - Hossain, Mohana; Rahman, Hosne Ara; Haque, Mahbubul; Rahman, Mahbubur; Hossain, Md Sanowar; Haque, Fatema Sultana; Begum, Rubina; Biswas, Shankar Kumar; Siddique, Md AB (Bangladesh Journal of Nuclear Medicine, 2015)
It is well established that Technetium99mmethylene diphosphonate (Tc99m MDP) whole body bone scintigraphy (WBBS) can demonstrate multiple lesions with increased radiotracer concentration in involved bone. But it is hard to differentiate multiple benign osteolytic lesions from disseminated bone metastases. Even combined with medical history and multiple imaging results, clinical diagnosis of metastatic lesion remains a challenge. This can affect the treatment procedure. Here the role of skeletal scintigraphy in a case of eosinophilic granuloma is evaluated and concluded that additional attention should be given before diagnosing any case as bone metastases. DOI: http://dx.doi.org/10.3329/bjnm.v17i1.22502 Bangladesh J. Nuclear Med. 17(1): 111-115, January 2014